Comparison between early gall bladder cancer and advanced gall bladder cancer in terms of clinicopathologic factors: large volume tertiary center experience - Chung, Hwe Hoon; Kim, Ji Eun; Chung, Kwang Hyun; Park, Joo Kyung (International Journal of Advances in Medicine, 2022)
Background: Early diagnosis of gallbladder cancer (GBC) which enables to surgical resection is key for improve prognosis. Aim of this study was to investigate clinical features of early GBC patients compare to advanced ones. Methods: We retrospectively reviewed medical records of all pathologically confirmed primary GBC patients between in single tertiary referral center. Results: 250 patients (57.3%) were early GBC (stage I and II) and 186 (42.7%) were advanced GBC (stage III and IV). Less patients with early GBC had symptom at initial diagnosis (69.2% versus 90.8%, p<0.001). Large number of patients with early GBC were diagnosed GBC incidentally after surgical resection which initially suspected benign gallbladder polyp or symptomatic gallbladder stones (71/250, 28.4% versus 7/186, 3.8%) (p<0.001). Patients who initially diagnosed gallbladder stone or cholecystitis tended to more advanced than gallbladder polyp. Conclusions: There were no definitive symptoms which can detect early GBCs. Large number of early GBCs were diagnosed incidentally and many of these initially diagnosed with or accompany with benign cholecystic disease. Careful examination should be performed before diagnosis and after treatment, even in patient with vague symptom or benign cholecystic disease without elevated tumor markers.